STRATEGI PENGEMBANGAN AGROINDUSTRI JAHE MERAH DI KOTA JAMBI (KASUS PADA AGROINDUSTRI JAHE KURNIA) - M, Nora Oktavia; Wahyuni, Ira; Ningsih, Rozaina (Fakultas Pertanian, Universitas Janabadra, 2024)
This research aims to describe the general picture of the Red Ginger agroindustry and analyze internal and external factors and calculate scores in the development of the Kurnia Agroindustry in Kenali Besar Village, Alam Barajo District. This research was carried out in Kenali Besar Subdistrict with 5 informants. The data used are primary and secondary data. Data were analyzed using descriptive methods, SWOT analysis (Strength, Weakness, Opposition, Threats) and AHP (Analytical Hierarchy Process) analysis. The research results from the SWOT matrix analysis show that the development of Kurnia Agroindustry in Kenali Besar District uses an SO strategy that combines strengths and opportunities so that optimal profits are obtained with the main priority that can be implemented, namely implementing an online sales system to overcome limited capital and high prices of raw materials.